Budesonidum limits survival ovarian cancer cells in vitro - Klaudia Nyga; Zuzanna Perkowska; Maciej Małecki (Polish Pharmaceutical Society, 2022)
Background Ovarian cancer is one of the most common and worst gynecological cancers. According to statistics, ovarian cancer ranks fifth among deaths from all cancer deaths in the female population in Poland. The low effectiveness of treatment is the reason for the constant search for new therapeutic solutions. Research results suggest a relationship between cancer development and chronic inflammation. A substance with well-defined anti-inflammatory therapeutic activity that can be used in research in other indications (oncology) is Budesonidum. Aim of the study The aim of the study was to evaluate the antitumor activity of Budesonidum in ovarian cancer cells. The research was carried out on the basis of the inhaled formulation of Budesonidum and in vitro using well-characterized ovarian cancer cell lines. Materials and methods The studies were carried out with the use of ovarian cancer cells of different type - adherent (Caov-3) and non-adherent (NIH: OVCAR-3). The effect of Budesonidum on cells of selected lines: cancerous and normal CCD-1064Sk (skin fibroblasts) in vitro was assessed. The cytotoxic activity of the drug on the cells was assessed on the basis of the cell survival results obtained by the MTT assay, IC50 calculations and photographic documentation of the cells by light microscopy. A wide range of Budesonidum concentrations from 2.32 µM to 232.27 µM was used. Results As a result of the research, it has been shown that Budesonidum has antitumor activity. The incubation of cells with the drug resulted in decreased cell viability. There was a correlation between the increase in the dose and the decrease in survival. It was estimated that the IC50 is higher for adherent cells (normal fibroblasts and Caov-3 ovarian cancer cells). Ovarian cancer cells of the adherent type have been shown to be the most resistant to Budesonidum. Ovarian cancer non-adherent cells (NIH: OVCAR-3) showed a higher sensitivity to Budesonidum. Conclusions Budesonidum shows antitumor activity against ovarian cancer cells. Ovarian cancer non-adherent cells (NIH: OVCAR-3), originally derived from the peritoneal exudate of patients, show high sensitivity to Budesonidum.